New data on the genus Platypalpus (Diptera: Hybotidae) from the Caucasus with description of seven new species - Kustov, Semen; Shamshev, Igor; Grootaert, Patrick (Zootaxa, 2015)
Currently, 47 species of the genus Platypalpus are known from the Caucasus including fourteen species recorded herein for the first time: P. albicornis (Zetterstedt, 1842), P. baldensis (Strobl, 1899), P. caroli Grootaert, 1987, P. ciliaris (Fallén, 1816), P. clarandus (Collin, 1926), P. collini (Chvála, 1966), P. cothurnatus Macquart, 1827, P. infectus (Collin, 1926), P. longicornis (Meigen, 1822), P. luteicornis (Meigen, 1838), P. nigrinus (Meigen, 1822), P. pseudociliaris (Strobl, 1910), P. ruficornis (von Roser, 1840), and P. smirnovi Kovalev, 1978. In addition, seven new species are described: P. akhunensis sp. nov. (Russia: Krasnodarskiy Territory), P. kintrishiensis sp. nov. (Georgia), P. lantsovi sp. nov. (Georgia), P. pseudosilvahumidus sp. nov. (Russia: Krasnodarskiy Territory, Karachay-Cherkessia), P. sinevi sp. nov. (Russia: Karachay-Cherkessia), P. subcaucasicus sp. nov. (Russia: Krasnodarskiy Territory, Dagestan) and P. teberdaensis sp. nov. (Russia: Karachay-Cherkessia). A key to species of Platypalpus from the Caucasus is presented for the first time.